Peran Job Crafting, Supervisor Support, Dan Pshycological Safety Terhadap Work Engagement Karyawan Industri Garment Di Kota Semarang - Alma Aulia Sari; Sjahirul Alim, Muchammad Rully; Salma Ida, Luluk (Universitas Muhammadiyah Pontianak, 2026)
This study examines the effect of competency development on job satisfaction and organizational commitment in improving employee performance at CV. Innovation Science Solution, Samarinda. Using a quantitative explanatory approach, data were collected from 43 employees and analyzed with SEM-PLS. The results show that competency development significantly influences job satisfaction, organizational commitment, and employee performance, both directly and indirectly through mediating variables. The findings imply that organizations should enhance competency development programs to improve satisfaction, strengthen commitment, and ultimately achieve better employee performance.